Digital Age Parenting and SDG 4.2: Examining Early Childhood Education Discourse in Mom's Corner Podcast - Khairiatul Nurwanti; Anzelia Anggrahini (Atfaluna: Journal of Islamic Early Childhood Education, 2026)
Purpose – This study examines how the Mom’s Corner podcast conceptualizes early childhood education (ECE) values in relation to Sustainable Development Goal (SDG) 4.2 indicators within the Indonesian context. Design/methods/approach – Using a qualitative content analysis design, this study investigated five purposively selected episodes (26, 36, 56, 65, and 72) of the Mom’s Corner podcast based on thematic criteria related to child development, school readiness, and educational inclusivity. Verbatim transcripts and audiovisual data were systematically processed through three stages of thematic coding: open, axial, and selective coding. Credibility was established via multi-framework triangulation incorporating ECE literature, Bronfenbrenner’s ecological systems theory, and official SDG 4.2 policy documents. Findings – The results reveal that the podcast explicitly advocates for holistic child development through targeted cognitive stimulation, responsive caregiving, socio-emotional bonding, and language acquisition. Furthermore, school readiness is framed as a multidimensional socio-behavioral construct, encompassing emotional maturity, self-regulation, and functional independence, rather than as a narrow focus on academic literacy. However, representations of educational inclusivity are profoundly constrained, omitting accommodations for children with disabilities and low-income demographics, thereby failing to fully operationalize the core SDG 4.2 ethos. Research implications/limitations – The primary limitation is the bounded qualitative focus on a single, prominent media channel, which confines the direct external generalizability of the findings to broader regional or non-corporate digital audio platforms. Practical implications – The study underscores that digital parenting media can serve as potent informal educational mechanisms to elevate parental literacy. It offers a clear rationale for policymakers to incorporate evidence-based digital content into national SDG 4.2 execution strategies while emphasizing the critical need for equitable digital infrastructure across marginalized communities. Originality/value – This research provides novel insights by empirically charting the intersections of modern digital discourse with institutionalized global educational benchmarks. Future research should evaluate longitudinal changes in parental behavior stemming from podcast consumption across diverse socioeconomic strata.